EFFECTS OF ORTHODONTIC TREATMENT ON PERIAPICAL HEALTH IN ENDODONTICALLY TREATED TEETH - Kantor Ianos; Sorana Maria Bucur; Ioana Todor; Ștefania Dinu; Cristina Nuca; Fulop Botond; Mariana Păcurar (Romanian Journal of Oral Rehabilitation)
This retrospective study evaluated the impact of orthodontic treatment on endodontically treated teeth. 32 teeth from 25 patients were analyzed, focusing on CBCT evaluations. All endodontic treatments utilized EDTA and 5.25% NaOCl in conjunction with Er:YAG laser-activated irrigation. Post-treatment assessment revealed that 21 teeth (66%) had root canal fillings of correspondent length, while 10 teeth (31%) were insufficient, and 1 tooth (3%) was uncertain. In terms of density and homogeneity, 25 teeth (78%) were classified as correspondent, 5 teeth (16%) as inadequate, and 2 teeth (6%) as uncertain. The periapical bone destruction probability index (PRI) demonstrated a significant increase in periapical destruction following orthodontic treatment. Specifically, the odds ratios for bone destruction were 1.67 (90% CI: 1.16–2.49, P=0.008) for present versus absent and 1.77 (90% CI: 1.11–2.85, P=0.031) for present versus uncertain. The proportion of teeth without periapical destruction decreased from 15 (14.9%) during treatment to 14 (23.9%) post-treatment. These findings highlight the critical relationship between endodontic quality and treatment outcomes, emphasizing the need for meticulous endodontics during orthodontic therapies.